A multi-campus usability testing study of the new Primo interface. Issue 1 (2nd January 2020) - Jacobs, W.; DeMars, Mike; Kimmitt, J. M.
Abstract: When the 23-member California State University Libraries merged integrated library systems in 2017, a unique opportunity arose to conduct multi-tenant usability testing on user experience in the Primo discovery service, collectively branded OneSearch. In 2018, librarians at five campuses conducted a round of task-based individual user testing on their separate instances, seeking to review individual campuses' decisions about customizations designed to provide optimal performance of the system and provide insight into group decisions about our shared customization choices. Along with the findings of the test results and recommendations for enhancements to existing modifications, we discuss the challenges and opportunities that are present in conducting multi-campus usability testing and share recommendations for future consortium-based testing efforts.